Antioxidants in Fish Sperm and the Potential Role of Melatonin - Francisca Félix; Catarina C. V. Oliveira; Elsa Cabrita (MDPI AG, 2020)
In recent years, the effects of novel antioxidants have played an important role in the research focusing on fish cell protection. As food demand grows, aquaculture production becomes more intensive, and fish are more exposed to oxidative stress conditions, like high densities, temperature shifting, frequent fish handling and samplings, and prophylactic or disease treatments, which expose fish to a different environment. Particularly in reproduction, germ cells lose antioxidant capacity with spermatogenesis, as spermatozoa are more prone to oxidative stress. Antioxidants have been used in a variety of fish physiological problems including in reproduction and in the establishment of cryopreservation protocols. From the most used antioxidants to natural plant food and herbs, and endogenously produced antioxidants, like melatonin, a review of the literature available in terms of their effects on the protection of fish spermatozoa is presented here in a classified structure. Several direct and indirect approaches to improve gamete quality using antioxidants administration are mentioned (through feed supplementation or by adding in cryopreservation media), as well as factors affecting the efficiency of these molecules and their mechanisms of action. Special attention is given to the unclear melatonin pathway and its potential scavenger activity to prevent and counteract oxidative stress damage on fish spermatozoa.